PENERBITAN SURAT KETERANGAN CATATAN KEPOLISIAN OLEH KEPOLISIAN TERHADAP CALON ANGGOTA LEGISLATIF YANG PERNAH MENJADI TERPIDANA BERDASARKAN P UTUSAN HAKIM BERKEKUATAN HUKUM TETAP (Studi Di Wilayah Hukum Polresta Pontianak) - NIM. A1012171162, AGUS SAPARUDIN (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACTIn the provisions of Article 240 paragraph (1) letter g of Law Number 7 of 2017 concerning Elections and Article 7 paragraph (1) letter g of General Election Commission Regulation Number 20 of 2018 concerning Nomination of Members of the People's Representative Council, Provincial Regional People's Representative Council, and Regency/City Regional People's Representative Council, there is a provision which states that all prospective members of the DPR, Provincial DPRD, and Regency/City DPRD must fulfill the requirement of